2008
DOI: 10.2118/101614-pa
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Flowback Analysis Using Polymer Concentrations and Fracturing-Fluid Tracer Methods: A Field Study

Abstract: Summary This paper compares flowback efficiencies using polymer concentration and frac fluid tracer methods. Results are presented for the flowback efficiency of each frac fluid segment using non-radioactive chemical frac tracers injected in a well, along with the results for the total flowback efficiencies using polymer concentration and frac fluid tracer analysis methods. Two wells were fraced and traced with various chemical frac tracers. Upon commencing flowback, samples of produced aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…If the reservoir permeability is high, then the fluid will invade the adjacent areas to the fracture face not deep in the fracture and fracture tip. In case of low permeability reservoirs, the fracturing fluids will penetrate the formation by increasing the fracture depths and so leakoff can take place through the fracture tip (Asadi et al 2008). Many factors can affect the flowback after fracturing job, such as pumping schedule, fluid type and the fracturing fluid chemistry (polymer loading, cross linkers and breakers).…”
Section: Flowback Of Fracturing Watermentioning
confidence: 99%
“…If the reservoir permeability is high, then the fluid will invade the adjacent areas to the fracture face not deep in the fracture and fracture tip. In case of low permeability reservoirs, the fracturing fluids will penetrate the formation by increasing the fracture depths and so leakoff can take place through the fracture tip (Asadi et al 2008). Many factors can affect the flowback after fracturing job, such as pumping schedule, fluid type and the fracturing fluid chemistry (polymer loading, cross linkers and breakers).…”
Section: Flowback Of Fracturing Watermentioning
confidence: 99%
“…Among existing flowback chemical analysis models (Asadi et al, 2008;Sullivan et al, 2004;Willberg et al, 1998;Woodroof et al, 2003), Gdanski et al (2007) was on of the first to incorporate a chemistry layer to a 2-D numerical simulator. This simulator was used to history-match the composition of flowback fluid.…”
Section: Spe 167164mentioning
confidence: 99%
“…This calls for a model that captures the transient 2-phase (gas/oil + water) flow in HF, and can be used for history matching rate and pressure data measured during flowback operations. Flowback chemical (tracer) analysis (Asadi et al, 2008;Sullivan et al, 2004;Willberg et al, 1998;Woodroof et al, 2003) could provide (1) an efficient means of differentiating formation water from flowback water (fracturing fluid + formation water) and (2) an optimal fracture clean-up or load recovery workflow.Developing an appropriate model for analysing rate/pressure measured during flowback operation requires a proper review of the static framework and flow physics of existing unconventional reservoir models. This paper extends the existing linear dual-porosity model (DPM) and develops a flowback analysis model (FAM) which accounts for transient multiphase flow in HF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding and modeling the recovery of gel filtercakes, whether permanently crosslinked with metals or reversibly crosslinked with boron, continues to be a subject of interest (Asadi et al 2008;Hutchins et al 2011). Field studies have indicated a positive correlation between gel recovery and gas productivity (Pope et al 1996).…”
Section: Introductionmentioning
confidence: 99%